Dynamical quantum phase transition in periodic quantum Ising chains. (9th September 2022) - Cao, Kaiyuan; Zhong, Ming; Tong, Peiqing
Abstract: The dynamical quantum phase transitions (DQPTs) after a sudden quench in periodic quantum Ising chains (QICs) are studied. We obtain the formulas of the Loschmidt echo and the Fisher zeros of the Loschmidt amplitude in the periodic QIC. It is found that for the quench across the quantum phase transitions (QPTs), the periodic QICs have richer DQPTs than that in the homogeneous QIC, and the number of critical times of the DQPTs are dependent on the specifical parameter of the pre- and post-quench Hamiltonian. For instance, in the period-two QIC, there is one critical time for the quench from the FM phase to the PM phase, and three critical times for the quench from the PM phase to the FM phase. In the period-three QIC, there may have three or four critical times for the quench from FM phase to the PM phase, but may have two or three critical times for the quench from PM to the FM phase. The reason is that the periodic QICs have multiple quasiparticle excitation spectra, and the Fisher zeros of the periodic systems consist of several separated branches, which is different from that in the homogeneous QIC. For different quenches across the QPTs, different branches will intersect with the imaginary axis, which correspond to different critical times. Our conclusion also provides insight in the property of the DQPT in the inhomogeneous systems.